(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research is to investigates the use of social media for students with disabilities at the university level and how it affects their academic and social lives. The study used the descriptive approach by developing a questionnaire, which was presented to a sample of 200 students from 5 different universities in UAE. The results found that there is less impact on the academic levels of students. However, the findings showed a negative impact of social media use on the social interactions of students. The participants of this study showed that they can use social media to expand their knowledge and get more information by using different platforms. Responses of the participants on the part related to social interaction showed negative implications. Students feel more isolated and alienated from physical interaction with other human beings.